2012
DOI: 10.1039/c2cc30957b
|View full text |Cite
|
Sign up to set email alerts
|

Hypergolic ionic liquids to mill, suspend, and ignite boron nanoparticles

Abstract: Boron nanoparticles prepared by milling in the presence of a hypergolic energetic ionic liquid (EIL) are suspendable in the EIL and the EIL retains hypergolicity leading to the ignition of the boron. This approach allows for incorporation of a variety of nanoscale additives to improve EIL properties, such as energetic density and heat of combustion, while providing stability and safe handling of the nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(112 citation statements)
references
References 17 publications
5
107
0
Order By: Relevance
“…We have investigated the use of boron(0) nanoparticles and, later, n ‐decaborane (B 10 H 14 ) to increase the energy density and reduce ignition delay of hypergolic ILs. We found that B 10 H 14 reacted with the ILs to form hypergolic boron hydride ions and isolated salts of [B 9 H 14 ] − with 1‐ethyl‐3‐methylimidazolium ([C 2 mim] + ) and N ‐butyl‐ N ‐methylpyrrolidinium ([C 4 mpyrr] + ), and these salts induced hypergolicity in nonhypergolic liquids.…”
Section: Figurementioning
confidence: 99%
“…We have investigated the use of boron(0) nanoparticles and, later, n ‐decaborane (B 10 H 14 ) to increase the energy density and reduce ignition delay of hypergolic ILs. We found that B 10 H 14 reacted with the ILs to form hypergolic boron hydride ions and isolated salts of [B 9 H 14 ] − with 1‐ethyl‐3‐methylimidazolium ([C 2 mim] + ) and N ‐butyl‐ N ‐methylpyrrolidinium ([C 4 mpyrr] + ), and these salts induced hypergolicity in nonhypergolic liquids.…”
Section: Figurementioning
confidence: 99%
“…Further, Rogers et al. have demonstrated that boron nanoparticles are high‐performance fuel additives for propellant applications, which can improve the flame performance of hypergolic ionic liquids to some extent 22. However, it has been shown that the presence of boron nanoparticles did not change the ID times for the hypergolic ionic liquids and only resulted in a small enhancement of the burn flame, which might be attributed to the boron ignition during the hypergolic reaction.…”
Section: Boron Chemistry: New Opportunity For Hypergolic Ionic Liquidmentioning
confidence: 99%
“…It is less sensitive to water in comparison with [BH 4 ] − and [Al(BH 4 ) 4 ] − . Also, boron is a source of energy as boron nanomaterials or elemental boron with hydrogen helps in the ignition of the fuel . By taking the advantage, it was focused on the [BH 3 CN] − and [DCA] − anions with pyridinium cation, which are thermally and chemically stable.…”
Section: Introductionmentioning
confidence: 99%